Examining the impact of demographic factors on the attitude of rural communities in Malaysia towards village WiFi services - Samsuddin, Samsul Farid; Bolong, Jusang; Omar, Siti Zobidah; Alby, Jeffrey Lawrence D'Silva; Sahharon, Hamisah; Mohamed Shaffril, Hayrol Azril (Canadian Center of Science and Education, 2015)
This study aims to examine the impact of demographic factors on the attitude of rural communities towards the village WiFi services. Data for the study were collected via a questionnaire, and based on multi-stage cluster sampling, a total of 400 villagers from four areas in Malaysia were selected as the respondents. The analysis performed confirms that there is a significant difference between males and females in terms of attitude towards village WiFi services, and that age and time spent using village WiFi services have a significant relationship with attitude towards village WiFi services. It is expected that this study will assist those concerned with formulating strategies to narrow the digital gap between rural community and technology.